Wine tasting at Dark Sky Alqueva, an exploratory study to wine sensorial experiences at night - Rodrigues (2022)
According to Dann and Jacobsen (2003) successful tourism destinations need to attract tourists by offering more than just visual stimuli and providing experiences involving all the senses. Wine tourism delivers a complete sensory experience, as tourists experience the consumption of wine from all senses: taste, smell, touch, sight, and sound. Traditionally the wine tourism experience can be provided in a number of ways, the most notable being events and festivals, cultural heritage, dining, hospitality, education, tasting and cellar door sales, and winery tours. With the growing of this type of tourism, wine tourism has to provide for the creation of unique and genuine tourism experiences, which must be more personalized and differentiated (Carvalho, Kastenholz & Carneiro, 2021). This study focuses on analyzing the different sensorial experience (taste, smell, touch, sight, and sound) of a blind-wine tasting experienced outdoors at night.